Lineamientos urbano resilientes; Caso de estudio: Macroproyecto, Altos de Santa Elena, Santiago de Cali, Colombia (2021)
This research study on Macroprojects of social interest is framed in the following line of research of the Antonio Nariño University: city and environment, because this research addresses social issues for the cultural and economic development of the territories, as well as It addresses ecological issues for the protection of the arboreal component and the fauna in the affected areas and seeks a connection of harmony between society and nature for a true sustainable development, in which this relationship is prioritized, to reach an effective resilience.